Kontribusi Pendidikan Islam Syaikh Ali Hasan Ahmad Ad-Dary - Zainal Abidin (Idrak: Journal of Islamic Education, 2018)
This paper describe the contribution of Syaikh Ali Hasan Ahmad Ad-Dary (scholars of hadis) on Islamic Education in North Sumatra. This research is the study of figures using library research. Islamic education activities in North Sumatra were initially held in the residences of preachers/ ulama and in various mosques as centers of Islamic activities as practiced Syaikh Hasan Ma’shum (1884-1937) in Medan, Syaikh Ja’far Abdul Qodir Al Mandily (1894-1958) and his younger brother Syaikh Muhammad Ya’kub Abdul Qodir Al Mandily (1914-1984) in Panyabungan, Madina. Then Islamic education developed and institutionalized with the founding of the establishment of the Musthafawiyah Islamic Boarding School in Purbabaru, Madina, Madrasah Maslurah (1912) and the Aziziyah Madrasah (1923) in Tanjung pura, Langkat, Maktab Islamiyah Tapanuli in Medan (1918) then the establishment of Islamic colleges and universities. In addition, the development of Islamic education in North Sumatra was also driven by several leaders/ scholars such as Syaikh Mustafa Husein, Syaikh Abdul Halim Khatib, Syaikh M. Arsyad Thalib Lubis and Syaikh Ali Hasan Ahmad Ad-Dary. Syaikh Ali Hasan Ahmad Ad-Dary's contribution in Islamic Education in North Sumatra is writing several Islamic education textbooks as a guide for students in the teaching and learning process, publishing and printing several Islamic education textbooks through his publishers Penerbit Al-Mahfuzh Budi, established several Islamic schools, madrasas anduniversities in North Sumatra. Syaikh Ali Hasan Ahmad Ad-Dary also participated in establishing the North Sumatra State Islamic Institute (IAIN SU).